القوس والسهم قبل التاريخ في عمان : مواد الصناعة ومصادرها - الماحي, علي التجاني (أدوماتو, 2013)
Keywords: Archéologie -- Oman

الرسوم الصخرية في وادي الجفر بسلطنة عمان : الدلالة و المعنى - الجهوري, ناصر سعيد (أدوماتو, 2013)
Keywords: Archéologie -- Oman

Tower-Fortresses of Ancient Magan: A study of the tower-fortresses of the third millenium on the Oman Peninsula - Botan, Sam A. (Leiden University, 2013)
The tower-fortress on the Oman Peninsula have always been a mystery to archeologists. A total of 15 tower-houses have been excavated or surveyed by archeologists in the past decades and yet their purpose inside the settlements is still poorly understood. This thesis analyzes and evaluates the existing theories about the tower-houses and offers an alternative theory by taking into account the locations, sizes and construction techniques of these buildings, using the survey and excavation rapports. The origins of the tower-fortresses can be found as early as the end of the fourth millennium B.C., when the settlement pattern on the Oman Peninsula shifts from the coast to the hinterland. The shift from the coast to the oasis brought a diversification of resources as well as a tighter appropriation of space. Combined with an increase in the copper trade at the beginning of the third millennium, this induced more complexity in the social system. The form of social organization which emerged on the Oman Peninsula due to these factors, was one which was in a liminal stage between a chiefdom and a state society, called a stratified non-state society. The tower-fortress of the Oman Peninsula functioned in such a society as dwellings and locus of regional power of a particular family or moiety. The few towers that have been excavated show many similarities, such as: he positioning of the towers within the settlements, the usage of a platform on which the towers rest, the interior of the platform consisting of two rows of chambers divided by a corridor or well, the ditches surrounding the towers and thus separating them from the rest of the settlement, the fact that all of the towers could only have been accessed by a ramp, etc. All of these similarities indicate specialization and one has to wonder if the possibility exists of a specialized class of tower-builders, travelling from settlement to settlement
Keywords: Archéologie -- Oman

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie -- Oman

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie -- Oman